Participation and social services local intervention in spain - Enrique Pastor Seller (Social Work and Society, 2016)
This article presents an analysis of the range opportunities for citizens' participation, in general, and of the social entities in particular - i.e. associative participation - in the design, implementation, follow-up and assessment of the public policies directing care services at a local level in Spain, as well as their possible influence on the agenda and management of local public policies for social welfare. The results of this research allow us to present a theoretical and regulatory framework of what is happening at a European and national level, as well as giving details about the autonomous regions of Spain. In the case of the autonomous communities, we must highlight the changes that new Social Services laws have brought about in terms of widening citizens' participation and opening up feedback for users of the system at a local level. In addition, this article discusses the role of different typologies and offer of mechanisms, bodies and process of participation in the design, management and assessment of social welfare policies at a local level. Finally, we determine the factors that help to increase the efficiency of social public policies, by means of an increase in citizens' participation in local governance.